PSYCHOLOGICAL FEATURES OF THE BACHELOR'S PERSONALITY IN THE PEDAGOGICAL PROCESS OF QUALITY CONTROL OF FUNDAMENTAL TRAINING - Ладогубець, H. B. (Proceedings of National Aviation University (archive), 2021)
Psychological and pedagogical aspects of quality control of fundamental training of bachelors of higher technical school are considered, taking into account the limitation of subjective actions of the teacher on the measurement result, on the one hand, and determination of psychophysiological features of each student, on the other hand. Certain types of quality control of fundamental training of bachelors depending on psychophysiological features of the bachelor's personality are offered.